Characteristics of Executive Acts of Bribery Under Art. 301, Para 1 and Under Art. 304, Para 1 Of Criminal Code - Mitreva, Petya (Research Papers, 2024)
The subject of the article are the executive acts of passive and active bribery under the Bulgarian Criminal Code. The author examines the issue if the forms of these acts are found in a subsidiarity ratio. This question is of determining importance both for the need of differentiation of criminal responsibility and for legal qualification of the criminal activity in case the bribery is committed with more than one act.